EVALUATION OF SOCIAL MOBILIZATION COMPONENT OF THE SECOND YEAR OF LIFE (2YL) PROJECT ON IMMUNIZATION COVERAGE IN ADAKLU DISTRICT, GHANA - Justice Kwesi BAAH; Justice NONVIGNON; Moses AIKINS; Genevieve C. ARYEETEY (Rojan GÜMÜŞ, 2022)
Ghana has had relatively high immunization coverage of more than 85% for infant antigens in the first year of life. However, there is a decline in immunization coverage for vaccines provided during the second year of life (2YL) of the child. As part of the 2YL project implemented in Ghana to strengthen the 2YL immunization platform, social mobilization strategies were utilized to help improve coverage for vaccines provided in the 2YL of a child. This study aims to evaluate the impact of social mobilization components of the 2YL project on immunization coverage in Adaklu district, Volta region, Ghana. In a pre-experimental design; a single-group pretest-posttest design was utilized to assess whether there was a significant change in immunization coverage pre-and post-intervention. Data on health facilities' immunization coverage were collected from DHMIS II (District Health Management Information System) before, during, and after the intervention. The Pearson chi-square, fisher's exact, Wilcoxon sign rank test, and paired t-test were used to evaluate the impact of the intervention implemented in 2017 on identified outcomes mainly Penta3, MR1, MR2, and MenA. The results indicated a significant improvement in the dropout rate between the first and second dose of MeaslesRubella vaccines in health facilities within the district. The number of health facilities that recorded a negative rate increased to 70% in 2018 from 25% in 2016. Also, the annual district immunization coverage for the Second dose of Measles (MR2) increased from 73% in 2016 to 84% in 2017 and 82.5% in 2018. In addition, Penta 3 coverage increased from 90.6% in 2016 to 100 plus % in 2017. The implementation of the social mobilization had a positive effect on immunization coverage in the district. The intervention resulted in increased immunization coverage and significantly reduced the measles Rubella dropout rate.